Data Profiling and Elections: Has Data-Driven Political Campaign Gone Too Far? - Yofira Karunian, Alia; Halme, Helka; Söderholm, Ann-Marie (Udayana Journal of Law and Culture, 2019)
In the age of digitalization, data-driven political campaign has rapidly shifted into sophisticated data profiling and big data analysis. In Indonesia, the privacy implications of data profiling for political purposes have not been thoroughly studied, much less regulated. This paper aims to conduct a comparative regulatory study between the European Union General Data Protection Regulation (EU GDPR) and Indonesian laws concerning personal data protection in facing the growing practice of data profiling for political purposes. In conclusion, in order to prevent unfair and non-transparent data profiling for political purposes in the upcoming 2019 general election, Indonesia should enact a comprehensive data protection law which provides data subjects with the right to information related to profiling and establishing independent supervisory authority.